Entangled Bodies: Jews, Bedouins, and the Making of the Secular Israeli. Issue 3 (3rd May 2016) - Razon, Na'amah
ABSTRACT: Taking Israel's National Health Insurance Law as a point of entry, in this article I probe how notions of equality and citizenship, secularism, and religion become entangled in the experience of Negev/Naqab Bedouins, who are Palestinian citizens of Israel. Drawing on ethnographic and archival research, I show how Jewish citizens have come to represent the secular and modern citizens in the region, while Bedouins, although mandated and claimed by policy and providers to be the 'same' and 'equal, ' are always already imagined and characterized as other. Universal health care and the daily manner in which biomedicine is practiced in southern Israel provides an avenue for examining the Jewish valences medicine carries in southern Israel, Israel's boundaries of inclusion, and the connection between biomedicine and secularism.